Edukasi Pemanfaatan Sampah Botol Plastik sebagai Media Hidroponik kepada Siswa Sekolah Dasar - Swarnawati, Aminah; Batunanggar, Muhammad Bayan Izzani; Juliyanto, Andri; Arifka, Angelia Ainun; Darman, Mayo Satria; Septianingsih, Wulandari (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
This Society’s service activity aims to educate the child as early as possible on the importance of taking care of the environment, by utilizing recycled plastic waste for greening around the house with hydroponic techniques. Limited greening is expected to reduce pollution. The implementation of the activities took place at SD Muhammadiyah 48 West Jakarta in August 2024. The activities included education regarding various important aspects of hydroponics, simple hydroponics training utilizing used bottles decorated as pots, planting squash and red spinach seedlings. The methods used are campaigns, lectures followed by training as well as demonstrations and last is planting practice. The result of this activity is that out of 15 seeds planted, 7 of them have developed into healthy shoots with a height of about 3 cm, while the rest are still in the process of germination. Squash seeds showed faster growth than red spinach seeds. This activity makes students love plants more, by utilizing waste into containers for hydroponics can also reduce waste in their living environment.